Understanding the role of "sunshine vitamin D" in Parkinson’s disease: A review - Behl, Tapan; Arora, Arpita; Singla, Rajeev K.; Sehgal, Aayush; Makeen, Hafiz A.; Albratty, Mohammed; Meraya, Abdulkarim M.; Najmi, Asim; Bungau, Simona Gabriela (Frontiers in Pharmacology, 2022)
After Alzheimer’s Disease, Parkinson’s Disease constitutes the second most widespread neurological disorder primarily affecting the older population. Its symptoms are noticeable with advancing age including tremors, postural imbalance, slow movements, and over time, these symptoms get aggravated, progressing to osteoporosis, osteopenia, and risk for fractures. These symptoms correlate to low bone density and hence, weakened bones, and thus, vitamin D proves to be an intricate component of the pathogenesis of the disease. Moreover, lower serum concentrations of vitamin D have been found in diseased subjects. Supplementation with vitamin D can retard the aggravation of non-motor as well as motor symptoms of Parkinson’s Disease that include cognitive improvement along with the decline in risk of fractures. Also, vitamin D is extremely crucial for brain functioning, targeting dopaminergic neurons and almost the entire functioning of the brain is affected. However, further exploration is required to determine the toxic dose of the vitamin in Parkinson's subjects. This ‘sunshine vitamin’ surely can be a ray of sunshine for neurologically diseased subjects.